HOW STUDENT ENGAGEMENT AND DECISION-MAKING SKILLS INFLUENCE BULLYING PREVENTION BEHAVIOR IN ADOLESCENTS: A CROSS-SECTIONAL STUDY - Masunatul Ubudiyah; Inta Susanti (Indonesian Journal of Community Health Nursing, 2026)
Introduction: Bullying is a global public health issue that predominantly affects adolescents in school settings and is associated with both short- and long-term adverse consequences. Student engagement and responsible decision-making represent essential soft-skill learning components that contribute to character development and play a critical role in bullying prevention. Therefore, this study aimed to examine the relationships between student engagement, decision-making capacity, and bullying behavior among adolescent students.   Method: This cross-sectional study involved 167 adolescent students from a public school and employed a purposive sampling technique. The variables assessed included student engagement and decision-making capacity, with bullying behavior serving as the dependent variable. All variables were measured using school bullying questionnaire, decision-making capacity questionnaire, Delaware student engagement scale that demonstrated established validity and reliability. Data were analyzed using Spearman’s rho correlation, with a significance level set at p ≤ 0.005.   Result: Most students demonstrated high student engagement and good to very good decision-making capacity, while bullying behavior was predominantly low. Significant negative associations were found between student engagement and bullying behavior (ρ = −0.273, p < 0.001) and between decision-making capacity and bullying behavior (ρ = −0.239, p = 0.002), indicating that higher engagement and stronger decision-making skills were associated with lower levels of bullying among adolescents.   Conclusion: Higher levels of student engagement and decision-making capacity were associated with lower bullying behavior among adolescents. These findings highlight the importance of strengthening student engagement and responsible decision-making skills as key components of school-based bullying prevention strategies.   Keywords: adolescent; bullying; decision making capacity; student engagement.